The Structure of Verbless Sentences in Northern Kurdish - Hasan, Aveen Mohammed (European Scientific Journal, ESJ, 2017)
In the study of syntax, a special attention is given to the verb as the main constituent in the structure of the predicate. However, there exists some constructions in which a noun, adjective or an adverb are the main constituents in the predicate. In Kurdish literature, there is a debate on the analysis of these verbless constructions. On one hand, they are considered nominal sentences which do not contain a verbal element. On the other hand, they are considered small verbal sentences in which the agreement markers on the predicate act as verbal element. The study is an attempt to analyse the structure of these verbless constructions within the framework of minimal program (Chomsky, 1995) in one of the widely spoken variety of Kurdish, Northern Kurmanji, Bahdinani subdialect. It contributes to resolve the existent debate in Kurdish linguistics concerning the structure of these constructions. Additionally, it contributes to the typological variation in the syntactic properties of these constructions in Kurdish.